Mental Health Among Medical Students During COVID-19: A Systematic Review and Meta-Analysis - Jia, Qingwen; Qu, Yi; Sun, Huiyuan; Huo, Huisheng; Yin, Hongxia; You, Dianping (Frontiers in Psychology, 2022)
Background: The mental health of medical students is an issue worthy of attention, especially during COVID-19. Many studies have shown that depression and anxiety are the main problems faced by medical students. To assess the pooled prevalence of depression and anxiety among medical students worldwide, we conducted this meta-analysis. Methods: According to PRISMA, we used a computerized strategy to search studies in EMBASE, PubMed, PsycArticles, Web of Science, and China Biology Medicine disc. The pooled prevalence of depression and anxiety was calculated by a random-effects model. Heterogeneity was explored by subgroup analysis. Sensitivity analysis and publication bias were also carried out in this meta-analysis. Results: Of 1316 studies, 41 studies were selected based on 36608 medical students. The pooled depression prevalence was 37.7% (95% CI: 30.7-45.4%), and pooled anxiety prevalence was 33.7% (95% CI: 26.8-41.1%). The prevalence of depression and anxiety among medical students varied by gender, country, and continent. Conclusions: The data reported that the prevalence of depression and anxiety among medical students during COVID-19 was relatively higher than those of the general population and the healthcare workers. The impact of COVID-19 on medical students and how to protect the mental health of medical students are needed to determine through further research.